ROLE OF RURAL WOMEN WORKING AS ACTORS OF LOCAL RURAL COMMUNITIES - Novakov, Marina (Economics of Agriculture, 2011)
The paper analyzes working role of rural women and conflicts of roles she takes during her life. Empirical part of analysis are qualitative research that was taken by author of this paper in four rural communities (Rumenka, Lipar, Mokrin and Popinci) on a sample of 300 women who have realized the role of motherhood.